Snakes from coastal islands of State of São Paulo, Southeastern Brazil - Cicchi, Paulo José Pyles [UNESP]; Sena, Marco Aurélio de; Peccinini-Seale, Denise Maria; Duarte, Marcelo Ribeiro (Instituto Virtual da Biodiversidade (BIOTA/FAPESP), 2007)
Há poucos estudos sobre a fauna de serpentes em ilhas costeiras do Estado de São Paulo, Sudeste do Brasil e um baixo número de espécies depositadas em coleções zoológicas. No Brasil, pela primeira vez, foi realizado um inventário em 18 ilhas do litoral paulista a partir de pesquisa de registros nas coleções herpetológicas do Sudeste do Brasil. Também foram realizadas coletas de campo em onze ilhas. Trinta e seis espécies de quatro famílias foram registradas: uma espécie de Boidae, trinta de Colubridae, uma de Elapidae e quatro de Viperidae. Os dados de campo apresentaram treze ocorrências novas de espécies sem registro nas coleções. Para estimar a raridade das espécies utilizaram-se categorias de abundância relativa: comum, não-freqüente e rara. Das espécies amostradas, 44,4% foram consideradas raras. As espécies mais comuns foram Micrurus corallinus, presente em doze ilhas; Bothrops jararaca e Liophis miliaris, presentes em onze ilhas, B. jararacussu e Chironius bicarinatus, presentes em 10 ilhas. Foram efetuados sete novos registros para a Ilha do Cardoso (25° 05 S e 47° 59 W): C. bicarinatus, C. multiventris, Dipsas petersi, Echinanthera bilineata, E. cephalostriata, Helicops carinicaudus e Xenodon neuwiedii; três para Ilha Comprida (24° 54 S e 47° 48 W): B. jararacussu, C. bicarinatus e H. carinicaudus; um para Ilha Anchieta (23° 32 S e 45° 03 W): Spilotes pullatus; um para a Ilha das Couves (23° 25 S e 44° 52 W): L. miliaris; um para a Ilha dos Porcos (23° 23 S e 44° 54 W): B. jararaca. B. alcatraz e B. insularis, endêmicos à Ilha de Alcatrazes e à Ilha da Queimada Grande, respectivamente, são considerados criticamente em perigo segundo IUCN. Foi registrada a extinção da fauna de serpentes na Ilha Monte de Trigo. Os ecossistemas insulares, mais vulneráveis que os continentais, carecem de uma proteção mais efetiva. A maioria destas espécies (cerca de 52%) preda anfíbios, reforçando a necessidade de conservação das florestas.

There are relatively few studies on snake fauna from coastal islands of the State of São Paulo (SSP), Southeastern Brazil and the number of species housed in Brazilian institutional zoological collections is relatively limited. In Brazil, for the first time, a snake inventory for eighteen islands of coastal SSP is presented. Here we record data from sampling on eleven islands as well information on vouchered species in the main herpetological collections. Thirty-six species from four families: one Boidae, thirty Colubridae, one Elapidae and four Viperidae from eighteen islands are listed as well as the thirteen new island records for snakes. Relative abundance categories were used for species rarity: common, infrequent and rare; 44.4% of the snakes with voucher specimens were considered rare. The most common species in twelve of the eighteen islands was Micrurus corallinus; in eleven of the eighteen islands were Bothrops jararaca and Liophis miliaris; in ten of the eighteen islands were B. jararacussu and Chironius bicarinatus. The most common snake species on coastal islands were Micrurus corallinus which was found in twelve of the eighteen islands, followed by Bothrops jararaca and Liophis miliaris found on eleven of the eighteen islands and B. jararacussu and Chironius bicarinatus which were found in ten of the eighteen islands studied. There are seven new records of snake species for Cardoso Island (25° 05 S and 047° 59 W): C. bicarinatus, C. multiventris, Dipsas petersi, Echinanthera bilineata, E. cephalostriata, Helicops carinicaudus and Xenodon neuwiedii; three new records for Comprida Island (24° 54 S and 47° 48 W): B. jararacussu, C. bicarinatus and H. carinicaudus; one for Anchieta Island (23° 32 S and 045° 03 W): Spilotes pullatus; one for Couves Island (23° 25 S and 44° 52 W): L. miliaris; one for Porcos Island (23° 23 S and 44° 54 W), B. jararaca. The endemic species B. alcatraz from Alcatrazes Island and B. insularis from Queimada Grande Island are considered endangered species by IUCN. Snake fauna on Monte de Trigo Island are extinct. The fragility of insular snake fauna needs more attention for environmental conservation, since 52.0% of snake species preys on amphibians, highlighting the importance of forest conservation.
Serpentes das ilhas costeiras do Estado de São Paulo, Sudeste do Brasil
Keywords: serpentes; ilhas; inventário; diversidade; conservação; snakes; coastal islands; inventory; conservation; diversity